Capital flows and current account sustainability: The Ghanaian experience - Maxwell Opoku-Afari (The University of Nottingham, Centre for Research in Economic Development and International Trade (CREDIT), 2007)
Both theoretical and operational definitions of current account sustainability show a persistent and fragile current account balance (deficit) for Ghana. This has created a financing gap in the Ghanaian economy, typically filled by capital inflows, in particular aid. Even as Ghana depends to a large extent on aid inflows it has tended to be procyclical. It is evident from the analysis that current account sustainability in Ghana is very sensitive to donor flow dynamics rather than trade flows. To make Ghanaian current account deficits sustainable a more stable and predominant trade contribution is required. Remittances from abroad are of increasing importance since 2000 and are relatively stable and counter-cyclical, and if managed can contribute to current account sustainability.
Keywords: F32; F35; F41; 330; Current Account; Sustainability; Capital Inflows; Leistungsbilanz; Zahlungsbilanzungleichgewicht; Ghana